Reconstructing the Meaning of Justice in the Qur'an: Integrating Izutsu’s Semantics and Arkoun’s Semiotics through a Spiral-Triadic Approach - Dwinuryudha Ken Rifqi; Andri Nirwana. AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Justice (al-‘adl) constitutes the moral core of the Qur’an; however, its interpretation within contemporary Islamic legal discourse has often stagnated due to the dichotomy between rigid textualism and unrestrained contextualism. This study aims to reconstruct the concept of justice through the framework of Noetic Legal Methodology, specifically the Spiral-Triadic Model. Employing a trans-epistemological library-based approach, the study integrates Toshihiko Izutsu’s semantic analysis and Mohammed Arkoun’s semiotic critique within a circular analytical movement (the Demystificatory Circular Process). The findings reveal three fundamental insights. First, at the bayani (textual) level, Izutsu’s semantics uncovers that ‘adl is not merely a legal concept but an ontological principle of balance (mizan) that underpins the Qur’anic Weltanschauung. Second, at the burhani (contextual) level, Arkoun’s critique of reason demystifies historical distortions, demonstrating how the meaning of justice has frequently been appropriated by power structures to sustain the status quo. Third, at the ‘irfani (synthetic) level, the integration of these approaches produces the notion of “liberative justice,” understood as a dynamic movement aimed at restoring social equilibrium guided by transcendental values. This study concludes that the proposed noetic synthesis offers a viable resolution to the methodological impasse in Qur’anic interpretation, repositioning justice as an emancipatory instrument relevant to contemporary humanity.